Clinical Impact of Revised Ciprofloxacin Breakpoint in Patients with Urinary Tract Infections by Enterobacteriaceae - Ga Eun Park; Jae-Hoon Ko; Sun Young Cho; Hee Jae Huh; Jin Yang Baek; Kwan Soo Ko; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (Antibiotics, 2021)
In 2018, the Clinical and Laboratory Standards Institute (CLSI) revised ciprofloxacin (CIP)-susceptible breakpoint for Enterobacteriaceae from ≤1 μg/mL to ≤0.25 μg/mL, based on pharmacokinetic-pharmacodynamic (PK-PD) analysis. However, clinical data supporting the lowered CIP breakpoint are insufficient. This retrospective cohort study evaluated the clinical outcomes of patients with bacteremic urinary tract infections (UTIs) caused by Enterobacteriaceae, which were previously CIP-susceptible and changed to non-susceptible. Bacteremic UTIs caused by Enterobacteriaceae with CIP minimal inhibitory concentration (MIC) ≤ 1 μg/mL were screened, and then patients treated with CIP as a definitive treatment were finally included. Patients in CIP-non-susceptible group (MIC = 0.5 or 1 μg/mL) were compared with patients in CIP-susceptible group (MIC ≤ 0.25 μg/mL). Primary endpoints were recurrence of UTIs within 4 weeks and 90 days. A total of 334 patients were evaluated, including 282 of CIP-susceptible and 52 of CIP-non-susceptible. There were no significant differences in clinical outcomes between two groups. In multivariate analysis, CIP non-susceptibility was not associated with recurrence of UTIs. CIP non-susceptibility based on a revised CIP breakpoint, which was formerly susceptible, was not associated with poor clinical outcomes in bacteremic UTI patients were treated with CIP, similar to those of the susceptible group. Further evaluation is needed to guide the selection of definitive antibiotics for UTIs.